2012
DOI: 10.1002/pola.26011
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of macromonomers into ring‐opening polymerization macroinitiators: A detailed initiation efficiency study

Abstract: In the present study, n-butyl acrylate macromonomer (BAMM) (M n ¼ 1900 g mol À1 ; PDI ¼ 1.96) has been synthesized via a high-temperature polymerization process. Subsequently, the olefinic termini of the BAMM have been transformed into a diol via a dihydroxylation process using KMnO 4 as an oxidizing agent. The OH-terminated macroinitiator pBA(OH) 2 has subsequently been employed for the ring-opening polymerization (ROP) of e-caprolactone via various catalytic systems, that is, organo-(1,5,7-triazabicyclo[4.4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…The established critical point of PCL in this study has never been reported. The advantage of the current critical conditions is an extended range of PCL molar mass compared to already reported critical conditions of PCL in aqueous mobile phase due to better solubility of higher molar mass PCL and higher pore size of the stationary phase , in line with the findings of Zorn et al . Such separation zone could be valuable for characterization of PCL‐containing block copolymers, polymer blends, and telechelic polymers, with an extended molar mass range.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The established critical point of PCL in this study has never been reported. The advantage of the current critical conditions is an extended range of PCL molar mass compared to already reported critical conditions of PCL in aqueous mobile phase due to better solubility of higher molar mass PCL and higher pore size of the stationary phase , in line with the findings of Zorn et al . Such separation zone could be valuable for characterization of PCL‐containing block copolymers, polymer blends, and telechelic polymers, with an extended molar mass range.…”
Section: Resultssupporting
confidence: 71%
“…1.0% TEA had to be added in the mobile phase to suppress undesired polar interactions (adsorption) of ether groups with free silanol groups of the stationary phase. The chromatographic critical conditions reported in this study possess several advantages compared to the earlier reports . Retention behavior of PCL at different mobile phase composition is demonstrated in Figure .…”
Section: Resultsmentioning
confidence: 89%
“…The versatility of the high temperature process was investigated by synthesizing an extensive MM library and by conducting postsynthetic steps toward more complex polymer architectures. In addition, improved microstructural control has been explored via controlled radical polymerization (CRP) also called reversible deactivation radical polymerization (RDRP) in which mediating agent species are present to control the microstructural growth of individual polymer chains. However, even under well-defined CRP conditions, reactions with MCRs led to the aforementioned formation of chain branches and the unavoidable loss of end-group functionality (EGF), especially under high-temperature conditions …”
Section: Introductionmentioning
confidence: 99%
“…30,31 Furthermore, MMs were applied in synthetic approaches to generate more complex materials out of these building blocks. 10,32 For the current study we aimed at applying the principle of MM synthesis from high-temperature acrylate polymerization to a precursor system in order to make identical acrylate MMs with low polydispersity. Therefore, poly(n-butyl acrylate) P(nBuA) polymers were synthesized via conventional ATRP.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Junkers and Barner-Kowollik refined the method of Chiefari et al and elucidated the reaction mechanism behind MM formation via detailed electrospray ionization mass spectrometry (ESI-MS) studies and kinetic simulations to explore the boundaries and limitations of MM synthesis and acrylate polymerization in general. , Indeed, it was shown that acrylate polymerizations at high temperature and conversion resemble (reversible) addition–fragmentation reaction systems, explaining why MMs of such high purity are accessible in the described way. Later, a diverse MM library was made using this approach, and the copolymerization behavior of n -butyl acrylate MMs was investigated. , Furthermore, MMs were applied in synthetic approaches to generate more complex materials out of these building blocks. , …”
Section: Introductionmentioning
confidence: 99%